Competencies Learned and Relevance of the Business Administration Curriculum to the Graduates’ Job - dela Cruz, Lilia Absin; Ferrater-Gimena, Judy Ann Ong; Inot, Perly Paquibot; Biore, Christopher (JPAIR Multidisciplinary Research, 2016)
The necessity for higher education is considered as an essential vehicle to alleviate a person’s productivity and employability. Many graduates find difficulty looking for suitable jobs nowadays. Any job opportunity even if not in line with the educational training is grabbed. This study gathered inputs on the competencies that the graduates of Bachelor of Science in Business Administration learned and the relevance of the program to their job. Furthermore, the result of the study aimed to improve the school’s quality education through the formulation of an intervention scheme that primarily focused on the transformation of the course syllabi to outcomes-based system. The study made use of descriptive-survey research design, adopting the standardized tool Graduate Tracer Study by the Commission on Higher Education (CHED). Utilizing purposive sampling, 52 graduates served as respondents. Findings showed that graduates were employable across various lines of businesses. The skills and competencies learned in college were relevant in their current jobs. However, relevant skills and competencies like communication skill and practical knowledge need to be enhanced so that future graduates of this program will have a competitive advantage in the labor market both locally and internationally. This issue can be addressed by improving the curriculum and the teaching-learning activities in the classroom that must be reflected in the course syllabi.